UKURAN PERUSAHAAN, PROFITABILITAS, FINANCIAL LEVERAGE, BOOX-TAX DIFFERENCES DAN KEPEMILIKAN PUBLIK TERHADAP PERATAAN LABA (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2014-2017) - Yasarah Diswari Ditiya; Sunarto Sunarto (Dinamika Akuntansi Keuangan dan Perbankan, 2019)
This research aims to examine the effect of firm size, profitability,financial leverage, boox-tax differences and public ownership structureto income smoothing at manufacturing companies listed on the Indonesian Stock Exchange (Bursa Efek Indonesia) in 2014-2017.The population in this research are Manufacturing Companies listed on the Indonesia Stock Exchange (Bursa Efek Indonesia). Sampling method using purposive sampling in the technique of data analysis is multiple linear regression analysis.The results of this research indicate that firm size, profitability, financial leveragehave a positif significant influence on Income Smoothing. Public ownership structurehave a negativesignificant effect on Income Smoothin whileboox-tax differences have no effect on Income Smoothing. Keywords: Firm Size, Profitability, Financial Leverage, Boox-Tax Differences, Public Ownership Structure, and Income Smoothing.